Medical image computing and computer assisted intervention - MICCAI 2023 / Part 9 - Greenspan, Hayit; Madabhushi, Anant; Mousavi, Parvin; Salcudean, Septimiu; Duncan, James; Syeda-Mahmood, Tanveer; Taylor, Russell (Medical image computing and computer assisted intervention - MICCAI 2023, 2023)
The ten-volume set LNCS 14220, 14221, 14222, 14223, 14224, 14225, 14226, 14227, 14228, and 14229 constitutes the refereed proceedings of the 26th International Conference on Medical Image Computing and Computer-Assisted Intervention, MICCAI 2023, which was held in Vancouver, Canada, in October 2023. The 730 revised full papers presented were carefully reviewed and selected from a total of 2250 submissions. The papers are organized in the following topical sections: Part I: Machine learning with limited supervision and machine learning - transfer learning; Part II: Machine learning - learning strategies; machine learning - explainability, bias, and uncertainty; Part III: Machine learning - explainability, bias and uncertainty; image segmentation; Part IV: Image segmentation; Part V: Computer-aided diagnosis; Part VI: Computer-aided diagnosis; computational pathology; Part VII: Clinical applications - abdomen; clinical applications - breast; clinical applications - cardiac; clinical applications - dermatology; clinical applications - fetal imaging; clinical applications - lung; clinical applications - musculoskeletal; clinical applications - oncology; clinical applications - ophthalmology; clinical applications - vascular; Part VIII: Clinical applications - neuroimaging; microscopy; Part IX: Image-guided intervention, surgical planning, and data science; Part X: Image reconstruction and image registration